DEVELOPMENT OF FUTURE MANAGERS' LEADERSHIP SKILLS IN EXTRACURRICULAR ACTIVITIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article regards some methodological approaches to the development of leadership skills of future managers. The author provides some scientific literature rewiew and shows specific organizational and pedagogical conditions and stages of leadership skills development.
Keywords: leadership skills, future managers, higher educational institution, organizational and pedagogical conditions, non-auditing activity.